(untitled) (Ius Novum, 2025)
The article analyses the case law of the Court of Justice of the European Union concerning ‘effective legal remedies’ under Article 14 of the Directive on the European Investigation Order (EIO) and ‘effective remedies’ provided for in EU directives regulating the rights of defendants in criminal proceedings. An analysis of this case law leads to the conclusion that the CJEU has established a more specific and higher standard of protection through effective remedies in the first of the aforementioned areas when interpreting Article 14 of the EIO Directive. By contrast, the case law on ‘effective remedies’ provided for in directives regulating the rights of defendants is based on the general assumption that EU law does not govern the admissibility of evidence, which means that it may sometimes be regarded as inconsistent with the standard established in this area by the European Court of Human Rights. The article also argues that the right to an effective remedy does not imply an obligation to create a separate legal measure in the form of a ‘complaint’ or ‘appeal’ within the national legal system.